Online Population Administration Services in Dukuhsari Village Governance Practice: Layanan Administrasi Penduduk Online dalam Praktik Tata Kelola Desa Dukuhsari - Azizi, Nadela Zakaria; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Digital transformation in public services encourages villages to adopt online administrative systems to improve service delivery. Specific Background: Dukuhsari Village implements the Plavon Dukcapil platform to manage population administration requests through a village-facilitated online process. Knowledge Gap: Limited empirical evidence explains how village institutions operationalize digital services amid infrastructure limits, digital literacy variation, and persistent offline preferences among residents. Aims: This study analyzes how village governance practices align with online population administration through goal achievement, integration, and adaptation perspectives. Results: Findings show strong institutional commitment, alignment between village goals and citizen needs, adequate facilities, and responsive staff support, while challenges include website delays, overlooked system notifications, limited waiting space, and KTP-EL blank shortages. Novelty: The study reveals how digital service implementation in rural settings depends not only on technology availability but on organizational readiness, physical facilities, and continuous digital literacy efforts. Implications: Insights inform village governments and policymakers on managing digital population services through organizational coordination, infrastructure support, and human resource preparedness.